A state-of-the-art review on tool wear and surface integrity characteristics in machining of superalloys. (November 2021) - Sarıkaya, Murat; Gupta, Munish Kumar; Tomaz, Italo; Pimenov, Danil Yu; Kuntoğlu, Mustafa; Khanna, Navneet; Yıldırım, Çağrı Vakkas; Krolczyk, Grzegorz M.
Graphical abstract: Highlights: A detailed review in the machining aspects of superalloys focusing in the machined surface integrity and cutting tool wear; The main aspects influencing machined surface integrity and cutting tool wear were identified as discussed; Based on the available data on the literature an optimization strategy to achieve optimum results is proposed. Abstract: Today, superalloys (also known as hard-to-cut materials) such as nickel, titanium and cobalt based cover a wide range of areas in engineering applications. At the same time, challenging material properties namely high strength and low thermal conductivity cause low quality in terms of cutting tool life and surface integrity of the machined part. It is important to improve the machinability of this type of materials by applying various methods in the perspective of sustainability. Therefore, current study presents surface integrity, tool wear characteristics and initiatives to improve them during the machining of superalloys. In this manner, it is outlined the surface integrity characteristics containing surface defects, surface roughness, microstructure alterations and mechanical properties. Also, tool wear mechanisms for example abrasive, adhesive, oxidation, diffusion and plastic deformation are investigated in the light of literature review. Finally, possible improvement options for tool wear and surface integrity depend on machining parameters, tool modifications, cooling methods and trade-off strategies are highlighted. The paper can be a guide for the researchers and manufacturers in the area of sustainable machining of hard-to-cut materials as explaining the latest trends and requirements.